A Comparative Risk Analysis of Semi-Organic and Inorganic Shallot Farming in Sukorejo Village Rejoso District Nganjuk Regency - Noor Rizkiyah; Nisa Hafi Idhoh Fitriana; Isfia Diana Putri (Agrisocionomics: Jurnal Sosial Ekonomi Pertanian, 2026)
The purpose of this research is to examine the production, pricing, and income risks as well as the distinctions between semi-organic and inorganic shallot farming in Sukorejo Village, Rejoso District, Nganjuk Regency. The study was carried out between November and December of 2024. This study was conducted using a survey of 75 shallot farmers selected through stratified random sampling. This study employed the Independent Sample T-test and Analysis of Risk (CV). The result indicate that production, price and income risk for both farming systems were generaly low. The factors contributing to the risks in production, price, and income included severe weather, pests and diseases, variable selling prices, and elevated farming costs. Statical testing showed no significant differences in production, price and income risks between semi organic and inorganic farming systems. The lack of difference was attributed to the similarity in land and irrigation practices for both semi-organic and inorganic forms, along with farmers' insufficient awareness regarding pure organic farming.